Journal Overlap Analysis of the GeoRef and Web of Science Databases. Issue 1 (2nd January 2016) - Kimball, Rusty
ABSTRACT: A journal overlap analysis was performed between the academic library databases GeoRef and Web of Science using Microsoft Excel with a third-party add-in for matching data in spreadsheets. The analysis determined that there were 555 journal titles common to both databases and that 4.13 percent of the 13, 437 GeoRef journals were found in Web of Science, and 2.84 percent of the 19, 489 Web of Science journals were indexed in GeoRef. This small percentage of geology journal coverage in Web of Science indicates that the use of this database would best be limited to lower-undergraduate assignments of geology students. This method of journal overlap analysis is fast and easy and can benefit both subject librarians and collection development departments.